2021
DOI: 10.1007/s12064-021-00357-3
|View full text |Cite
|
Sign up to set email alerts
|

Information transmission in a two-step cascade: interplay of activation and repression

Abstract: We present an information-theoretic formalism to study signal transduction in four architectural variants of a model two-step cascade with increasing input population. Our results categorize these four types into two classes depending upon the effect of activation and repression on mutual information, net synergy, and signal-to-noise ratio. Using the Gaussian framework and linear noise approximation, we derive the analytic expressions for these metrics to establish their underlying relationships in terms of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…We exclude results for n > 2, say n = 3, etc as the functions f x and f y are highly nonlinear in this regime. The results obtained using higher-order nonlinear functions show disagreement between theory and simulation [26].…”
Section: J Stat Mech (2023) 093502mentioning
confidence: 72%
See 2 more Smart Citations
“…We exclude results for n > 2, say n = 3, etc as the functions f x and f y are highly nonlinear in this regime. The results obtained using higher-order nonlinear functions show disagreement between theory and simulation [26].…”
Section: J Stat Mech (2023) 093502mentioning
confidence: 72%
“…In many cases, however, one observes a non-degenerate response. In a recent study [26], AA and AR motifs were found to collate with respect to the fidelity of signal transduction (measured as signal-to-noise ratio). In addition, RA and RR motifs were also found to have a collating nature with respect to the said metric.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches are the following: (i) Gaussian approximations of the input to make use of analytic results [12], (ii) Monte Carlo estimators [13], [32], [33]. (iii) Not rarely, the intractability decoyed researchers to resort to other channels such as the Gaussian channel [34], [35]. We contribute to information theory in biology by presenting a Monte Carlo-free numerical computation of the path mutual information rate of a Poisson channel for Markovian input with low state number.…”
Section: B Path Mutual Information In Cell Signalingmentioning
confidence: 99%
“…Another study characterises the signalling fidelity in the TSC motif by measuring redundancy based on PID formalism [21]. The architecture dependent information transmission on four different variants of TSC motifs has been studied by Roy et al [22]. In one of our previous studies [23], we showed the role of intermediate node X in the TSC motif in information transmission where we used the formalism of Shannon's MI and Schreiber's TE for bivariate and multivariate information transfer along with the formalism of PID.…”
Section: J Stat Mech (2022) 123502mentioning
confidence: 99%